(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
"Boburnoma", which is considered a rare example of the world memoir genre, has gained attention as an encyclopedic work. In the work, not only the external appearance of historical figures, but also their character, inner world, spiritual world, mentality, dreams, and interests are skillfully revealed. This article is devoted to the issue of word psychology in "Boburnoma".